2018
DOI: 10.2478/jdis-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Trends in Complementary and Alternative Medicine Applied in Cancer-Related Symptoms

Abstract: Purpose:The main goal of this study is to discover the scientific evolution of Cancer-Related Symptoms in Complementary and Alternative Medicine research area, analyzing the articles indexed in the Web of Science database from 1980 to 2013.Design/Methodology/Approach: A co-word science mapping analysis is performed under a longitudinal framework (1980 to 2013). The documental corpus is divided into two subperiods, 1980-2008 and 2009-2013. Thus, the performance and impact rates, and conceptual evolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Furthermore, the theme of Breast Cancer is composed of several relevant articles 48-52 mainly focused on the treatment of the cancer-related symptoms, highly researched also in the literature. 53 This finding is entirely in concordance with the social and economic repercussion of the breast cancer condition, 54 since it ranks second (15.4%) among cancer deaths after lung cancer in the developed nations. England has the highest relative interest in this theme.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the theme of Breast Cancer is composed of several relevant articles 48-52 mainly focused on the treatment of the cancer-related symptoms, highly researched also in the literature. 53 This finding is entirely in concordance with the social and economic repercussion of the breast cancer condition, 54 since it ranks second (15.4%) among cancer deaths after lung cancer in the developed nations. England has the highest relative interest in this theme.…”
Section: Discussionsupporting
confidence: 59%
“…The most related themes in a cluster network of "Waste Management Systems" are "Waste Collection", "Waste Generation", and "Source Separation". This could suggest that the themes are weakly (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) incorporated and lacking in salience (Cobo et al, 2011;Moral-Munoz et al, 2018a;Moral-Munoz et al, 2018b). In this study, the theme "Environmental Impact Assessment" is firmly tight to "Ecosystem" and "Comparative Study".…”
Section: 3mentioning
confidence: 65%
“…Table 4 depicts the performance method of the themes in the second period. In this period, the motor theme "Municipal Solid Waste" presents the highest publication (797), h-index (52), and a strong position as the most vital theme (Cobo et al, 2011;Moral-Munoz et al, 2018a;Moral-Munoz et al, 2018b). Although the motor themes "Waste Disposal Facility", "Waste to Energy", and "Costs" has a fewer number of publications; the themes had provided an adequate h-index.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…They also discovered the scientific evolution of cancer-related symptoms in complementary and alternative medicine (CAM) research area and identified the main research thematic by using the coword analysis. The coword analysis identified 12 main thematic areas including anxiety, survivors and palliative care, and meditation [ 8 ]. Jose's research studies can reflect the difference between CAM and ICM.…”
Section: Introductionmentioning
confidence: 99%